Late Arteriovenous Fistula after transurethral resection of the prostate: case report - Matheus, Marina Bertolini; Degani, Arthur; Domenico, Bruno; Freire, Lucas Marcelo Dias; Ferreira, Ubirajara; Matheus, Wagner Eduardo (Brazilian Journal of Case Reports, 2023)
This study describes a case of symptomatic arteriovenous fistula after Transurethral Resection of the Prostate diagnosed by urethrocystoscopy and confirmed by imaging tests. The patient presented lower urinary tract symptoms associated with hematuria twenty years after being submitted to a TURP. Arterial and venous tomography angiography of the pelvis visualized a hypervascularized lesion involving the membranous urethra and aneurysm of the right external iliac artery. The patient underwent embolization of bilateral prostatic arteries with good post-embolization recovery and complete remission of urinary symptoms. Arteriovenous fistula after transurethral resection of the prostate is a rare pathology that must be considered in the differential diagnosis of persistent hematuria and infravesical obstruction without significant prostatic enlargement. In cases like this, embolization has become a new therapeutic option with excellent obliteration rates and minimal morbidity.